nRF Transceiver Based Accident Diminution System with Automatic Brake Lock - Dr.B.Nagajayanthi, Sai Praneeth G , Siva Ram Dinesh U, Sujit Kumar Rayani (International Journal of Advanced Science and Technology, 2020)
The intelligent transportation system is emerging in a vehicular ad-hoc network. nRF based vehicle network is trending in the field of automation to communicate between vehicles in real-time. RF transceiver-based accident diminution system with automatic brake lock is targeted to thwart calamities. Intelligent transportation systems are trending in IoT for traffic management and smart information transfer. A warning signal is generated on the dashboard when vehicles are viable to crash. This is achieved using Wi-Fi and RF modules which wirelessly broadcast and communicate with each other. An Ultrasonic sensor is used to detect and determine the distance between nearby vehicles. An Infrared sensor is used as a tachometer to calculate the speed of the vehicle. Speed and distance thresholds in terms of rpm and received signal strength set an alarm in the dashboard. In an emergency, if the driver is not able to respond to the warning signals, the vehicle brake is automatically applied. Apart from vehicles, V2V communication could communicate with traffic lights to regulate traffic flow depending on the density of the users. Using the nRF Transceiver module, a virtual map is created and the status of the nearby vehicles alerts distracted drivers in case of black spots i.e. mainly at intersection points. These features help in avoiding collisions to a major extent using the vehicle to vehicle communication